B Cell Activation, Differentiation, and Their Potential Molecular Mechanisms in Osteoarthritic Synovial Tissue - Lu P; Li Y; Yang S; Yao H; Tu B; Ning R (Journal of Inflammation Research)
Peizhi Lu,1,2,* Ya Li,1,2,* Shuo Yang,2 Haoyu Yao,2 Bizhi Tu,2 Rende Ning1,2 1Graduate School, Bengbu Medical University, Bengbu, Anhui, People’s Republic of China; 2Department of Orthopedics, the Third Affiliated Hospital of Anhui Medical University, the First People’s Hospital of Hefei, Hefei, Anhui, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bizhi Tu, Department of Orthopedics, the Third Affiliated Hospital of Anhui Medical University, the First People’s Hospital of Hefei, Hefei, Anhui, People’s Republic of China, Tel +86 15357483840, Email 1301535636@qq.com Rende Ning, Graduate School, Bengbu Medical University, Bengbu, Anhui, People’s Republic of China, Tel +86 13956966305, Email nrd1972@outlook.comObjective: The objective of this study was to characterize the activation and differentiation of B cells in the synovium of osteoarthritis (OA) and to explore the underlying molecular mechanisms.Methods: Peripheral blood and synovial samples from OA patients at different stages were collected, and flow cytometry was employed to analyze the activation and differentiation of B cells. Immunofluorescence staining of joint synovium from OA mice at different stages was conducted to assess mice joint synovium B cell activation and differentiation. Co-culture experiments of synovial fibroblasts with B cells were performed to investigate the influence of synovial cells on B cell activation and differentiation. Finally, transcriptome analysis was utilized to identify potential key molecules and pathways.Results: In OA patients, the infiltration, activation, and differentiation of B cells in synovium and peripheral blood exhibited distinct characteristics. Specifically, the proportion of activated CD86+ B cells and the differentiation marker HLA-DR+ increased with disease severity, whereas the proportion of the differentiation marker IgM decreased. The proportion of CD38+ B cells also decreased with increasing severity, although this change lacked statistical significance. Immunofluorescence staining of CD19+ and CD86+ cells in mice indicated increased expression with greater OA severity. Co-culture experiments demonstrated that OA synovial fibroblasts promoted B cell activation and differentiation, as evidenced by higher expression levels of CD86+ and HLA-DR+ in the OA group compared to controls. Additionally, the proportion of naive B cells decreased as disease severity progressed.Conclusion: Synovial fibroblasts in OA have been shown to promote the differentiation and activation of B cells, indicating that B cells play a significant role in the pathogenesis of synovium inflammation in OA.Keywords: osteoarthritis, B cells, inflammation, immune, transcriptome sequencing, synovium